FORMATION OF SPEAKING CULTURE IN MORAL AND AESTHETIC EDUCATION OF AUDIENCES (Multidisciplinary Journal of Science and Technology, 2024)
The purpose of the article is to study the importance of developing the culture of public speaking in the moral and aesthetic education of students, and to propose mechanisms for improving the quality of public speaking education in schools. The article analyzes the current state of speech education in schools, identifies problems that prevent the development of speech culture, suggests strategies for improving the formation of speech culture in schools. In addition, the article highlights the importance of the formation of public speaking culture in the moral and aesthetic education of students. The authors note that the ability to speak effectively is an important skill for personal, academic, and professional success, and that developing this skill can increase students' self-confidence, creativity, critical thinking, and social skills.